Efektifitas Komunitas Belajar dalam Mendukung Implementasi Kurikulum Merdeka pada SMA Negeri 9 Ambon - Edi Suprapto; Josef Papilaya; Arnold Sahalessy (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
The implementation of the Independent Curriculum in self-registered schools faces challenges, particularly limited understanding and resource support. This study aims to assess the effectiveness of learning communities in supporting the Independent Curriculum at SMA Negeri 9 Ambon. Using a qualitative descriptive approach through interviews, observations, and documentation, the study found that learning communities serve as forums for discussion, collaborative material development, and reflective teaching practices. The main obstacles include lack of structured planning and limited funding, yet teacher involvement and school leadership still enhanced curriculum comprehension. The findings confirm that learning communities effectively foster collaboration and strengthen the learning ecosystem. The study recommends sustainable funding and stronger inter-school networks to optimize curriculum implementation